Pengolahan Air Limbah Batik Jambi Menggunakan Filtrasi dan Fotokatalisis TiO2 (Titanium Dioksida) - Suzana, Asih; Adriansyah, Endi; Herawati, Peppy; Marhadi, Marhadi; Silvina, Tris; Sufra, Rifqi (Universitas Batanghari Jambi, 2024)
Batik production process generates liquid waste primarily from dyeing and de-waxing processes. This waste, if not managed properly, can pose environmental challenges. This study explores the potential of Eco-photocatalysis using TiO2 (Titanium Dioxide) for treating wastewater from the batik industry. The process involves utilizing ultraviolet (UV) light and a catalyst to enhance the degradation of parameters such as pH, TSS (Total Suspended Solids), and color. Using a reactor containing four 8-watt UV lamps and maintained agitation at 1100 rpm. The catalyst used is Titanium Dioxide (TiO2) (3 grams). The procedure encompassed varying contact times (60, 120, and 180 minutes) and lamp quantities. The results demonstrate that TiO2-assisted Eco-photocatalysis effectively reduces organic and inorganic pollutants in treated water till pH, 6,73, TSS 70 mg/L and color 0,99 Pt-Co.